Diode Laser‐Crystallization for the Formation of Passivating Contacts for Solar Cells. Issue 5 (8th March 2022) - Gawlik, Annett; Glatthaar, Raphael; Dellith, Andrea; Jia, Guobin; Dellith, Jan; Terheiden, Barbara; Plentz, Jonathan
Abstract : A new method of diode laser treatment of passivating contacts for solar cells application based on electron beam evaporated highly doped amorphous silicon (a‐Si) layers deposited on solar‐grade Czochralski wafers with SiOx tunneling layers is investigated. In a first step, an interface oxide is grown and a highly doped n‐type a‐Si layer is deposited on both sides by electron beam evaporation. In a next step, the laser treatment is applied. Two different scanning speeds of 15 and 20 mm s −1 are used. Electron backscattering diffraction and quasi‐ steady‐ state photo conductance measurements indicate that the a‐Si layer can be crystallized without breaking up the thin oxide layer. To determine the best parameters, the lifetime and the implied open‐circuit voltage for each laser power are measured. The first results show a fitted lifetime of 4.06 ms and an implied open‐circuit voltage up to 711 mV after a passivation step. Abstract : A new method of laser treatment of passivated contacts for wafer solar cell application was investigated. The Czochralski wafer samples were deposited with highly doped amorphous silicon layers on both sides. The samples are scanned with two different speeds and the corresponding power densities. A fitted lifetime above 4.06 ms and an implied open‐circuit voltage of 711 mV were achieved.